Możliwości wprowadzania Mindtoyness do wczesnej edukacji. Ewaluacja z perspektywy społeczno-organizacyjnej i badawczej - Jolanta Kruk (Problemy Wczesnej Edukacji)
The article continues the issues surrounding the Mindtoynessproject, carried out between 2019 and 2021. Its summary would not be complete if it were not accompanied by a broader, social reflection on the context in which it arose and was developed. This context consists of: the change in perceptions and cognitive processes in the digital turn, turbulent social background, as a consequence of the COVID-19 pandemic together with the reforms of the education system in Poland. When evaluating the MT project, it is also worth pointing out the possibilities of introducing the kits at the level of early childhood education, confronting them with the current core curriculum. Other aspects of project evaluation concern the possibility of conducting research at a distance, as an unavoidable consequence of a pandemic situation and conclusions relating to the differences associated with the different cultural contexts in which the researcher and collaborating actors work.